Use of hydraulic modeling to assess the performance of fire-fighting water supply networks - Ścieranka, Grzegorz; Jendroszczyk, Anita; Grajper, Paweł; Krzeszowski, Światosław (Instal, 2025)
The article examines how hydraulic modeling, using EPANET, supports the assessment of fire-fighting performance in water supply networks. It compares two approaches to hydrant simulation: fixed discharge and free outflow dependent on pressure. The study demonstrates that free-outflow modeling more accurately reflects real hydrant behavior, enabling better evaluation of whether required fire flows can be achieved, especially when multiple hydrants operate simultaneously or when network conditions are unfavorable. The results show that hydraulic models are essential for analyzing fire scenarios, verifying network capacity, and supporting decisions on design, modernization, and operational reliability of water  distribution systems.
Keywords: water supply network; Epanet; hydraulic modeling; fire hydrant